Software Engineering Proceedings of CSI 2015 - Hoda, M. N.; Chauhan, Naresh; Quadri, S. M. K.; Srivastava, Praveen Ranjan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents selected proceedings of the annual convention of the Computer Society of India. Divided into 10 topical volumes, the proceedings present papers on state-of-the-art research, surveys, and succinct reviews. They cover diverse topics ranging from communications networks to big data analytics, and from system architecture to cyber security. This book focuses on Software Engineering, and informs readers about the state of the art in software engineering by gathering high-quality papers that represent the outcomes of consolidated research and innovations in Software Engineering and related areas. In addition to helping practitioners and researchers understand the chief issues involved in designing, developing, evolving and validating complex software systems, it provides comprehensive information on developing professional careers in Software Engineering. It also provides insights into various research issues such as software reliability, verification and validation, security and extensibility, as well as the latest concepts like component-based development, software process models, process-driven systems and human-computer collaborative systems.
Chapter 1: A Multi-Agent Framework for Context Aware Dynamic User Profiling for Web Personalization -- Chapter 2: Implementation of Equivalence of Deterministic Finite State Automation and Non-Deterministic Finite State Automaton in Acceptance of Type-3 Languages Using Programming Code -- Chapter 3:A Multi - Factored Cost and Code Coverage Based Test Case Prioritization Technique for Object Oriented Software -- Chapter 4: A Novel Page Ranking Mechanism Based on User Browsing Patterns -- Chapter 5: Indexing of Semantic Web for Efficient Question Answering System -- Chapter 6: A Sprint Point Based Tool for Agile Estimation -- Chapter 7: Improving Search Results Based On Users' Browsing Behaviour Using Apriori Algorithm -- Chapter 8: Performance Efficiency Assessment for Software Systems -- Chapter 9: Impact of Programming Languages on Energy Consumption for Sorting Algorithms -- Chapter 10: Crawling Social Web With Cluster Coverage Sampling -- Chapter 11: Efficient Management of Web Data by Applying Web Mining Pre-processing Methodologies.
Keywords: Software engineering; Software engineering -- Management; Computer science; Software Engineering; Software Management; Computer Science Logic and Foundations of Programming